Investigation of Using Plastic Waste in Asphalt Concrete Mixture as Binder Modifier - ABDUL AZIZ, MUHAMMAD AZHAN; Shamshuddin, Mustafa Kamal (Recent Trends in Civil Engineering and Built Environment, 2021)
Indirect tensile strength test (ITS) have been performed as performance test of asphalt concrete mixture according to Marshall standard gradation type AC14. There is a detrimental environmental effect of plastic waste products. The reuse of plastic waste will enhance the properties in engineering construction projects such as road paving bitumen and mixtures of asphalt. In order to decrease harmful of plastic waste to the environment, it have been reused in asphalt concrete mixture as aggregate replacement. The purpose of this study is to investigate the suitability of using plastic waste in asphalt concrete mixture and to evaluate the durability of asphalt mixture with plastic waste. This scope focused on the parameters of indirect tensile strength. The plastic waste used in this study was in the form of granules of about 3 mm diameter which PET type mineral bottles and the proportion used for this study about 0.2, 0.4 and 0.6% of percentage plastic waste. Method that had been used in this study was indirect tensile strength test with Marshall procedure to conduct the study. The result from the performed test showed that plastic waste also suitable for asphalt modifier in certain percentage such as less than 0.2%. This is because of more percent of plastic was added, it will reduce the durability of the asphalt concrete due to lose the original characteristics of asphalt concrete mixture but it still relevant to use as asphalt modifier in order to create potential to reduce the pollution. Utilization of plastic waste was satisfying for asphalt concrete performance. For the recommendation, the plastic waste to be used as a modifier in asphalt concrete must not exceed 0.2 percent as it will reduce the durability of asphalt concrete mixture. Performing another more tests in detail using same percentage of 0.2% to obtain more criteria with respect to the decrease in durability of the asphalt concrete.